2022
DOI: 10.1001/jamanetworkopen.2022.43225
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Housing Affordability and Severe Maternal Morbidity

Abstract: ImportanceThe number of people living in unaffordable housing (relative to income) is projected to continue increasing as housing cost inflation outpaces incomes in the US. Although reproductive-aged women have disproportionately high housing costs, particularly around the time of childbirth, data on associations between housing costs and maternal health and the role of publicly supported affordable housing programs in mitigating those associations are lacking.ObjectiveTo estimate associations between area-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…There is abundant literature documenting potential risk factors for SMM, such as early or advanced age, lower socioeconomic status, and obesity. 29,[40][41][42][43] To provide new insights for SMM prevention, we focused on environmental risk factors that have not been examined previously. We observed that experiencing more heat days during pregnancy was associated with increased risks of SMM, where risks increased as heat exposure became more extreme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant literature documenting potential risk factors for SMM, such as early or advanced age, lower socioeconomic status, and obesity. 29,[40][41][42][43] To provide new insights for SMM prevention, we focused on environmental risk factors that have not been examined previously. We observed that experiencing more heat days during pregnancy was associated with increased risks of SMM, where risks increased as heat exposure became more extreme.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant literature documenting potential risk factors for SMM, such as early or advanced age, lower socioeconomic status, and obesity . To provide new insights for SMM prevention, we focused on environmental risk factors that have not been examined previously.…”
Section: Discussionmentioning
confidence: 99%
“…Unhoused patients suffer from decreased life expectancy, 2 high morbidity and mortality, and significant barriers to receiving health care 3 . Median housing costs have risen consistently for the past 10 years, and housing instability has been linked to poor cardiovascular health 4,5 . Governmental and institutional health care support for unhoused patients in the United States varies widely by region, and significant disparities in care exist 6 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Median housing costs have risen consistently for the past 10 years, and housing instability has been linked to poor cardiovascular health. 4,5 Governmental and institutional health care support for unhoused patients in the United States varies widely by region, and significant disparities in care exist. 6 The average life expectancy of unhoused patients in the United States is 54.14 years, while patients in the top 1% of earnings have a life expectancy of up to 87.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, maternal mortality continues at unacceptably high rates in the US and in many low- and middle-income countries; national immigration policies that affect the health of adults have spillover effects on children’s health; US Medicaid and other nations’ policies on access to care for children affects long-term educational and employment outcomes into adulthood; policies on LGBTQ rights have implications for mental health and medical and surgical care; and firearm regulations affect outcomes in the medical, surgical, and mental health arenas across populations . The economy, always a priority for voters, has effects on mental health as well as the ability to afford health care and meet other essential needs like education, housing, sanitation, food, and water that are social drivers of health . Moreover, stagnated investments in health, health care, and health care systems worldwide portend a failure to meet health-related Sustainable Development Goals .…”
mentioning
confidence: 99%